Uveitic Glaucoma: Long-term Clinical Outcome and Risk Factors for Progression. (2nd November 2017) - Sharon, Yael; Friling, Ronit; Luski, Moshe; Campoverde, Belén Quizhpe; Amer, Radgonde; Kramer, Michal
ABSTRACT: Purpose : To study the long-term clinical outcomes of uveitic glaucoma and to identify risk factors for progression. Methods : Retrospective study of uveitic glaucoma patients in two tertiary medical centers in 2003–2015. Patient- and disease-related data was retrieved. Clinical parameters and visual fields measured at predetermined time points were recorded. Outcome measures included maintaining intraocular pressure ≤21 mmHg and preserving visual fields. Results : Included were 34 patients (53 eyes), with a mean follow-up of 7 years. Idiopathic anterior uveitis and open-angle glaucoma were most common. In total, 62% of eyes were steroid responders. Higher IOP was associated with posterior synechiae, peripheral-anterior synechiae, steroidal, and immunomodulatory therapy ( p <0.05). Glaucomatous field defects developed in 49%, with most showing no progression, despite elevation of cup-to-disc ratio ( p <0.05). Conclusions : Chronic severe uveitis, expressed by structural complications and immunomodulatory therapy, was associated with high IOP and the need for more IOP lowering medications, but was unrelated to glaucomatous damage.